A perspective on regional and global strategies of multinational enterprises - Rugman, Alan M; Verbeke, Alain (Journal of International Business Studies, 2004)
Multinational enterprises (MNEs) are the key drivers of globalization, as they foster increased economic interdependence among national markets. The ultimate test to assess whether these MNEs are global themselves is their actual penetration level of markets across the globe, especially in the broad ‘triad’ markets of NAFTA, the European Union and Asia. Yet, data on the activities of the 500 largest MNEs reveal that very few are successful globally. For 320 of the 380 firms for which geographic sales data are available, an average of 80.3% of total sales are in their home region of the triad. This means that many of the world's largest firms are not global but regionally based, in terms of breadth and depth of market coverage. Globalization, in terms of a balanced geographic distribution of sales across the triad, thus reflects a special, and rather unusual, outcome of doing international business (IB). The regional concentration of sales has important implications for various strands of mainstream IB research, as well as for the broader managerial debate on the design of optimal strategies and governance structures for MNEs.